African Great Lakes and Rivers Working Group – Collaboration through practical demonstration - Lewis, Tim; Swadling, Nick (The International Hydrographic Review, 2025)
This note highlights the successful collaboration between industry, Member States of the Southern African and Islands Hydrographic Commission (SAIHC) African Great Lakes and Rivers Sub Working Group (AGL&RsWG) and other organisations. Malawi hosted, through the Ministry of Lands and most AGL&RsWG members were represented. An initial meeting in Lilongwe was followed by a demonstration day at Monkey Bay, sponsored by Kongsberg Maritime AS, Sensors & Robotics division*, delivered by GeoSystems. The United Kingdom Hydrographic Office (UKHO) funded attendance for AGL&RsWG members. Outcomes included, a greater awareness of shared challenges faced by regional stakeholders and collaborative solutions to maximise resources.